PENGARUH METODE VTS (VISUAL THINKING STRATEGY) TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS X SMK SWASTA MARKUS 2 MEDAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Visual Thinking Strategy (VTS) learning method on the ability of tenth-grade students at SMK Swasta Markus 2 Medan to write procedural texts. The research employs a quantitative approach. The population consists of all tenth-grade students at SMK Swasta Markus 2 Medan. The sampling technique used is cluster random sampling (random selection based on class groups), in which two classes are randomly selected from three tenth-grade classes consisting of 60 students, resulting in a sample of 40 students. The instrument used in this study is a subjective test in the form of an essay. After applying different treatments, the results show that the mean score of the pretest is 61.25 with a standard deviation of 8.66, while the mean score of the posttest is 78.5 with a standard deviation of 33.70. The prerequisite test results indicate that the data are normally distributed and homogeneous. Furthermore, a one-tailed t-test (α = 0.05) is conducted. Based on the results of the t-test, it can be concluded that there is a significant effect of the Visual Thinking Strategy (VTS) learning method on students' ability to write procedural texts in the tenth grade at SMK Swasta Markus 2 Medan, with the final results categorized as good. Keywords: Visual Thinking Strategy (VTS) method, writing ability, procedural texts